An indicator framework for assessing cooperative cross-border conservation in the Karakoram-Himalayan region - Jie Li (Elsevier, 2021)
The Karakoram-Himalayan (KH) region comprises high mountains across seven countries (i.e., China, Afghanistan, Pakistan, India, Nepal, Bhutan, and Myanmar) with a variety of management regimes and priorities and capacities for conservation. Currently, there is no comprehensive framework for assessing cooperation on protected areas (PAs) in the KH region. Such a framework is essential to guide managers and policymakers in the formulation of consistent management plans and strategies for regional sustainable development. In this study, an indicator framework for assessing cooperation on PAs was developed based on four factors: the natural environment, the human environment, transport accessibility, and the diplomatic environment. The assessment involved 49 cross-border national parks and nature reserves in this region. Furthermore, the indicators were analyzed by using the analytic hierarchy process, resulting in eight cross-border groups. The analysis reveals that the region has a good foundation for cooperative cross-border conservation in general. Among the eight groups, the Karakoram-Pamir, Kangchenjunga, and Everest groups exhibit greater potential for closer cooperation, whereas the Kashmir group has a lower basis for cooperation. The results suggest that the establishment of transboundary conservation areas (TBCAs) and academic and scientific development can provide opportunities to enhance our understanding of the KH region and to collaborate across national boundaries. This case study explains that the indicator framework can be used as a reference for cooperative cross-border conservation in other regions worldwide.